2003
DOI: 10.1136/qhc.12.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Can health care quality indicators be transferred between countries?

Abstract: Objective: To evaluate the transferability of primary care quality indicators by comparing indicators for common clinical problems developed using the same method in the UK and the USA. Method: Quality indicators developed in the USA for a range of common conditions using the RAND-UCLA appropriateness method were applied to 19 common primary care conditions in the UK. The US indicators for the selected conditions were used as a starting point, but the literature reviews were updated and panels of UK primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 8 publications
2
114
0
4
Order By: Relevance
“…14 Other European workers 25,26 have identified that there may be country-specific factors, such as differences in clinical practice, that preclude the direct transfer of quality indicators from the U.S. to the U.K.. Indeed, our work supports their view.…”
Section: "They Reduce the Risk But Is Failure To Prescribe A Drug-resupporting
confidence: 79%
“…14 Other European workers 25,26 have identified that there may be country-specific factors, such as differences in clinical practice, that preclude the direct transfer of quality indicators from the U.S. to the U.K.. Indeed, our work supports their view.…”
Section: "They Reduce the Risk But Is Failure To Prescribe A Drug-resupporting
confidence: 79%
“…This is relevant to the health policies used by different health systems to externally assess and improve their quality of practice management. We see ''considerable benefits in using work from other settings'' to help modify existing indicators of quality (rather than develop indicators de novo) (21), and refine the structures in which quality can be assessed and improved. This paper has therefore considered lessons that NZ experience of externally assessing practices for accreditation, whilst encouraging quality improvement, might have for European general practice.…”
Section: Resultsmentioning
confidence: 99%
“…8 Therefore, the purpose of this study was to develop and validate a set of structure and process QIs to measure the organization of palliative care in different health-care systems and countries, taking geographical, historical, political, and cultural aspects into account. 9 This study was co-funded by the European Executive Agency for Health and Consumers (EAHC) and part of the Europall project, in which experts in palliative care from seven European countries (Belgium, United Kingdom, France, Germany, Netherlands, Poland, and Spain) participated. The Europall project ran from October 2007 till September 2010.…”
Section: Introductionmentioning
confidence: 99%